Analisis Keterampilan Dribbling Permainan Futsal pada Remaja Putus Sekolah di Desa Suka Maju Bengkulu Utara - Toha, Muhammad (UNIVED Press, Universitas Dehasen Bengkulu, 2020)
Based on the researcher's observations on the implementation of school dropout soccer game activities in Suka Maju Village, North Bengkulu Regency, that the researcher wants to analyze the football skill level of School Dropout Youth in Suka Maju Village, North Bengkulu Regency. This research method is quantitative descriptive. The population of this study was all 20 school dropouts in Suka Maju Village, North Bengkulu Regency. The place for the research was carried out in the futsal field in Suka Maju Village, North Bengkulu Regency, while the research time was April 2018. Data on dribbling skills were taken using the physical freshness center theory dribbling test. The data analysis technique of this research uses techniques with quantitative data analysis. The results of the data analysis show that: The basic skills of futsal dribbling for school dropouts in rural villages like Bengkulu Utara. With 9 people in the good category with a relative frequency magnitude of 45%, 9 people in the medium category with a relative frequency magnitude of 45%, 1 person in the less category with a frequency magnitude of 5% and 1 person in the very poor category with a frequency magnitude of 5%. Meanwhile, the average skills of rural school dropouts like to advance are in the medium category with a score of 49.5.